Gender dalam Perspektif Aliran Feminisme: Analisis Wacana tentang Hakikat dan Kedudukan Perempuan - Nurmadani Nurmadani; M. Rama Darmawan; Firdaus Danny (Journal of Gender and Millennium Development Studies, 2025)
Background: Studies on gender issues remain an important topic of debate in social, cultural, and academic contexts, especially in relation to how women are positioned within deeply entrenched patriarchal systems. Objective: The objective of this research is to analyze feminist texts from various schools of thought, including liberal, radical, Marxist, socialist, and postmodern feminism, to understand how these perspectives contribute to the broader conversation on gender equality and justice. Method: This research employs a qualitative method, focusing on the analysis of feminist texts from different schools of thought. Data were collected through a comprehensive literature review, and the analysis involved examining representations of women and the use of language that reflects ideology and power relations. Result; Although each feminist school has its own approach, all aim to advance gender equality and justice. They offer valuable insights into how gender roles are constructed and influenced by power and ideology. The research highlights that understanding gender as a social construct shaped by culture and power is key to driving social change. Conclusion: Gender is not a fixed biological characteristic but a social construct shaped by cultural and power dynamics. The research underscores the importance of interpreting feminist perspectives in a contextual and critical manner to foster more equitable social change. It highlights the need for gender-responsive approaches that respect the diversity of women's identities and experiences. Contribution: This study contributes to the broader understanding of feminist theory and its application in promoting gender justice and equality in contemporary society.